2018
DOI: 10.15171/apb.2018.006
|View full text |Cite
|
Sign up to set email alerts
|

Novel Combination of Silver Nanoparticles and Carbon Nanotubes for Plasmonic Photo Thermal Therapy in Melanoma Cancer Model

Abstract: Purpose: Plasmonic photo thermal therapy (PPTT) is a therapeutic method in which the photon energy is rapidly transformed into heat via a series of radiative and non-radiative phenomena to ablate cancer. Plasmonic NPs, such as silver NPs (Ag NPs), have considerable properties in optical absorbance. Furthermore, good thermal conductivity and cell penetration ability of carbon nanotubes (CNTs) could improve the efficacy of Ag NPs for PPTT. Decoration of the multi-walled carbon nanotubes (MWCNTs) with silver has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 44 publications
0
35
0
Order By: Relevance
“…Studies have shown that after PTT on a murine melanoma cell line B16/F10, histopathology showed cell necrosis of up to 70% and 60% for CNTs/Ag and CNTs, respectively. 105 The same group tested murine melanoma tumor cells with surface modified MWCNTs in which the CNTs were oxidized and then treated with a layer of PEG. This time, cellular necrosis using oxidized MWCNTs coated with a layer of PEG showed more than 90% necrosis (at 1 mg/mL of each sample injected into the tumor at a dose of 200 μL/cm 3 of tumor volume), while the control group only showed 25% necrosis after receiving an 808 nm continuous-wave NIR laser at an intensity of 8 W/cm 2 for 10 min of therapy.…”
Section: Cnts In Photothermal/dynamic Therapymentioning
confidence: 99%
“…Studies have shown that after PTT on a murine melanoma cell line B16/F10, histopathology showed cell necrosis of up to 70% and 60% for CNTs/Ag and CNTs, respectively. 105 The same group tested murine melanoma tumor cells with surface modified MWCNTs in which the CNTs were oxidized and then treated with a layer of PEG. This time, cellular necrosis using oxidized MWCNTs coated with a layer of PEG showed more than 90% necrosis (at 1 mg/mL of each sample injected into the tumor at a dose of 200 μL/cm 3 of tumor volume), while the control group only showed 25% necrosis after receiving an 808 nm continuous-wave NIR laser at an intensity of 8 W/cm 2 for 10 min of therapy.…”
Section: Cnts In Photothermal/dynamic Therapymentioning
confidence: 99%
“…They tuned to absorb laser beam energy at a specific range of wavelengths. 1 Titanium dioxide (TiO2) appears in the world as familiar mineral crystals such as anatase and rutile. 2 TiO2 is efficient to transform solar energy into electrical energy.…”
Section: Introductionmentioning
confidence: 99%
“…Silver has been employed for biomedical purposes since ancient time owing to its anti-microbial properties 17 , 18 . Recent researches on Dalton's lymphoma ascites tumor model 19 , glioblastoma- or melanoma-bearing mice 20 , 21 , and lung or breast cancer-bearing mice 22 - 24 have demonstrated the efficacy of silver NPs (AgNPs) in suppressing tumor growth. More recently, we reported a pure physical method, which avoided the use of any hazardous biological and chemical reducing agents, to fabricate ultra-small silver particles reaching the Ångstrom (Ång; one-tenth of nanometer) sizes 16 .…”
Section: Introductionmentioning
confidence: 99%